The Effect of Service Quality and Promotion on Shopee Market Place Purchase Satisfaction (Case Study on Students of Management) - Eva Nanda Wulandari; Fitri Ayu; Fina Ramasari Br Nasution; Frengki Jaya Putra; Anjani Intan (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This research is quantitative to answer questions about the influence of service quality and promotion on purchase satisfaction in the Shopee marketplace. Data collection was conducted by distributing questionnaires to 100 Shopee marketplace customers at Panca Budi University. The model used is Multiple Regression and processed using SPSS. The research results indicate that service quality and promotion together (simultaneously) have a positive and significant impact on consumer purchase satisfaction. Service quality has a positive and significant impact on purchase satisfaction in the Shopee marketplace. The promotion has a positive and significant impact on purchase satisfaction in the Shopee marketplace. The determinant coefficient, in this case, means that 82.5% of consumer purchase satisfaction can be obtained and explained by service quality and promotion.